Kajian Hubungan Unsur Iklim Terhadap Produktivitas Cabe Jamu (Piper retrofractum Vahl) di Kabupaten Sumenep - Eko Setiawan (Agrovigor, 2009)
The study was conducted to determine the relationship between productivity long peppers (Piper retrofractum Vahl) with the elements of climate (rainfall, number of monthly rainfall, air temperature, and humidity) and utilize the extent that relationship to estimate production. Data collected with the survey and the relationship is determined by analyzing the coefficients correlation. Results of regression with productivity long peppers is Y equal 10,567 + 3.90 (X1) -0012 (X2) - 0078 (X3). Determinasi coefficient value (R2) of 0.82 or 82%. This indicates that the influence of independent variables (weather elements) can be explained on the dependent variable (production) of 82%. While 18% of the productivity of long peppers described by other independent variables that are not included in the model.